Komparasi Hasil Belajar Matematika Ditinjau Dari Status Sosial Ekonomi Orang Tua dan Motivasi Belajar pada Siswa Kelas XI Semester Ganjil SMK Bhina Karya Karanganyar Tahun 2015/2016 - Werdiningsih, Indah, Drs. Ariyanto,M.Pd (2016)
The background of this study is the low result of learning mathematics in SMK Bhina Karya Karanganyar. The cause may come from within the students that the students' motivation and socio-economis status of parents. The aim of research to describe and analyze: (1) the differences in mathematics learning outcomes of socio-economic status of parents, (2) the differences in mathematics learning outcomes of the level of student motivation, (3) the interaction between socio-economic status of parents and the level of students motivation to learn math results.The type of this research is comparison. The population of the research was all students of XI grade of SMK Bhina Karya Karanganyar of odd semester of academic year 2015/2016. The researchsample consisted of three classes. The sampling technique use random sampling. Methods of data collection use questionnaire and documentation. . Data analyzed by analysis of variance with two different cell lines. The results of data analysis with a significance level of 5% was obtained: (1) there is differences in mathematics learning outcomes of socio-economic status of parents, with (2) there is differences in mathematics learning outcomes of the level of student motivation, with (3) there is no interaction between socio-economic status of parents and the level of students motivation to learn math results, with FAB=1,33.